Biocompatibility of resin-based dental materials applied as liners in deep cavities prepared in human teeth - Costa, Carlos Alberto de Souza [UNESP]; Teixeira, Hilcia Mezzalira; Nascimento, Alexandre Batista Lopes do; Hebling, Josimeri [UNESP] (Wiley, 2007)
Background: Since only a few data have been published concerning the effects of resinous dental materials on the pulp-dentin complex, the aim of this study was to evaluate the biocompatibility of resin-based materials applied as liners in deep cavities prepared in duman teeth. Methods: After preparing class V cavities, the following dental materials were applied on the axial walls: group 1, Vitrebond™ (VIT; 3M ESPE); group 2, Ultra-Blend® Plus™ (UBP; Untradent); and group 3, Clearfil™ SE Bond (CSEB; Kuraray). In group 4 (control), the hard-setting calcium hydroxide cement Dycal (CH; Caulk/Dentsply) was used. The teeth extracted at 7 days or between 30 and 85 days after the clinical procedures were processed for histological evaluation. Results: For all the experimental and control groups, most of specimens exhibited no pulpal response or slight inflammatory reaction associated with slight tissue disorganization at 7-day period. Moderate inflammatory pulpal response occurred only in one tooth (RDT = 262 μm) of group 3 in which transdentinal diffusion of resin components was observed. Conclusion: The resin-based dental cements VIT and UBP as well as the bonding agent CSEB presented acceptable biocompatibility when applied in deep cavities prepared in sound human teeth. © 2006 Wiley Periodicals, Inc.
Keywords: Biocompatibility; Dental materials; Dentin; Human tooth; Pulp; Dental cement; Dentistry; Histology; Hydrated lime; Medical problems; Deep cavities; biomaterial; calcium hydroxide; resin; tooth cement; biocompatibility; controlled study; dentin; diffusion; evaluation; histology; human; inflammation; tooth pulp; Adolescent; Biocompatible Materials; Child; Dental Cavity Lining; Dental Materials; Humans; Materials Testing; Resin Cements; Tooth